Spatial variability and convergence of the coupled relationship between agricultural carbon emission reduction and rural revitalization in China - Hongli Yang; Kai Feng (Frontiers in Sustainable Food Systems)
IntroductionPromoting the coupled and coordinated development of agricultural carbon emission reduction and rural revitalization is a key link and an inevitable choice to achieve the goal of “double carbon” and sustainable rural development.MethodsThis study takes 31 provinces (cities) in China (excluding Hong Kong, Macao and Taiwan) from 2010 to 2022 as the research object, and adopts the entropy value method, the coupling coordination degree model, the Gini coefficient and its decomposition, and the convergence degree model, etc., to analyze the level of coupling coordination between agricultural carbon emission reduction and rural revitalization in terms of spatial and temporal development characteristics, regional differences and convergence.Results and discussionThe study found that: (1) the coupling and coordination level of agricultural carbon emission reduction and rural revitalization at the national level and in the four major regions continues to improve, and the type of coupled coordination in the provinces is dominated by “primary coordination” in 2022; (2) inter-regional differences are the main source of differences in the coupling and coordination level of agricultural carbon emission reduction and rural revitalization in China; (3) There is no σ-convergence in the coupled coordination level of agricultural carbon emission reduction and rural revitalization at the national level, but there are significant absolute β-convergence and conditional β-convergence, and there are some differences in the regional convergence characteristics, and there is obvious regional heterogeneity in the development of external factors on the coupled coordination level in different regions. The results of the study provide strong empirical support and important practical guidance for an in-depth understanding of the current situation and trend of the coupled and coordinated development of agricultural carbon emission reduction and rural revitalization, in order to explore effective ways to promote the synergistic progress of the two.